In Vivo Efficacy of Purified Quillaja Saponin Extracts in Protecting against Piscirickettsia salmonis Infections in Atlantic Salmon (Salmo salar) - Hernán Cortés; Mario Castillo-Ruiz; Hernán Cañon-Jones; Trinidad Schlotterbeck; Ricardo San Martín; Leandro Padilla (Animals, 2023)
Piscirickettsiosis, the main infectious disease affecting salmon farming in Chile, still has no efficient control measures. Piscirickettsia salmonis is a facultative intracellular bacterium that can survive and replicate within the host macrophages, evading the immune response. Triterpenic saponins obtained from the Quillaja saponaria tree have been widely studied, and have been shown to be immunomodulatory agents, suitable for feed and vaccine applications for veterinary and human uses. The impact of the oral administration of two extracts of Quillaja saponins on the infection of P. salmonis in Salmo salar and the corresponding gene expressions of immunomarkers were studied under three in vivo models. In the intraperitoneal challenge model, the group fed with Quillaja extracts showed lower mortality (29.1% treated vs. 37.5% control). Similar results were obtained in the cohabitation model trial (36.3% vs. 60.0%). In the commercial pilot trial, the results showed a significant reduction of 71.3% in mortality caused by P. salmonis (0.51% vs. 1.78%) and antibiotic use (reduction of 66.6% compared to untreated control). Also, Quillaja extracts significantly modulated the expression of IFN-II and CD8. These results represent evidence supporting the future use of purified Quillaja extracts as a natural non-pharmacological strategy for the prevention and control of P. salmonis infections in salmon.